Timeliness Disclosure of Financial Reporting In Indonesian Mining Companies - Fauziah, Dona; Jumaiyah, Jumaiyah; Aliyah, Siti (Jurnal Minds: Manajemen Ide dan Inspirasi, 2020)
This study aims to investigate empirical evidence about factors that affect the timeliness of financial reporting of mining companies listed on the Indonesia Stock Exchange. This research method uses quantitative methods. The sample selection is using a purposive sampling method. The data obtained were then tested using logistic regression analysis at a significance level of 5%. The results of the study identified that company size and profitability had a positive effect on the timeliness of financial reporting. In contrast, institutional leverage and ownership do not affect the timeliness of financial reporting of mining companies listed on the Indonesia Stock Exchange.